Furniture decoration of the grand interiors in the suburban estates of the Sheremetyev counts. The role of the customer and the architect - Kochetkova, Anastasiya Dmitrievna (Философия и культура, 2025)
The subject of this research is the interaction between the client and the architect in the formation of the atmospheric complex of Moscow interiors during the Neoclassical era, with the object being the furniture decor of the ceremonial halls in the suburban estates of Kuskovo and Ostankino, owned by the Sheremetyev counts. The methodological basis of the research implies the application of a sociological approach, as well as various methods used in contemporary art studies. Through comparative analysis of preserved furniture items and architectural graphics, as well as the study of archival documents, the author concludes how significant the role of the client was in Moscow when designing the interior ensemble. In contrast to St. Petersburg, even at an early stage of Neoclassical development in Moscow, the client acted as a full co-author of the architect: not only did he actively express his requirements and wishes regarding the final result, but he also repeatedly "edited" the proposed designs. This scenario is clearly illustrated by the activities of Count P. B. Sheremetev, who articulated his artistic ideas at a high professional level. However, this approach became particularly pronounced by the end of the century, with the spread of the phenomenon of "country house amateurism." For instance, Count N. P. Sheremetev, who received an excellent European education, was an undisputed arbiter of taste in organizing the spatial environment of Moscow interiors. It is precisely away from the strict regulations of the Court that the estate's space becomes a fertile ground for testing the client's original creative ideas. The conclusions drawn from the research allow for a clearer picture of the distinctive character of the furniture decor of secular interiors in the Moscow context and significantly expand the existing understanding of private commissions during the Age of Enlightenment.